Identification of Mutations in SDR9C7 in Three Patients with Autosomal Recessive Congenital Ichthyosis - Juliette Mazereeuw-Hautier; Maella Severino-Freire; Véronique Gaston; Hélène Teixer; Marie Vincent; Hélène Aubert; Fanny Morice-Picard; Nathalie Jonca (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)